Odpowiedzi

2009-11-11T15:29:08+01:00
SO3+H2O=H2SO4
MgO+H2O=Mg(OH)2
2Na+2H2O=2NaOH+H2
Fe+O2=Fe2O3
2Al(OH)3+3H2SO4=Al2(SO4)3+6H2O
2009-11-11T15:44:43+01:00
SO₃+H₂O -> H₂SO₄
MgO + H₂O -> Mg(OH)₂
2Na + H₂O -> Na₂O + H₂
4Fe + 3O₂ -> 2Fe₂O₃
2Al(OH)₃ + 3H₂SO₄ -> Al₂(SO₄)₃ + 6H₂O


----------------------------------------
Co do Fe (III) i Na(I) nie wiem o co CI konkretnie chodzi więc napiszę do każdego po 2 różne reakcje:P

4Fe + 3O₂ -> 2Fe₂O₃
Fe₂O₃ + 3H₂O -> 2Fe(OH)₃

Na₂O + H₂O -> 2NaOH
2NaOH + H₂SO₄ -> Na₂SO₄ + 2H₂O